Olhares sobre a cidade e a regi\~ao - por que importam? Enfoques e metodologias disciplinares e contraditórias de análise do território para políticas públicas - Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The paper discusses the city and the region aiming at unfolding a synthetic panorama of the various ways of thinking and acting upon the spatial issue. We argue that a better understanding of how the different scientific disciplines with interfaces on the territory view and work with space allows more adequate public policy designing. The paper assumes that socioeconomic activity holds a continuum and interpedently connected influence upon urban and regional areas. Further, a second objective of the paper is to referee the reader from different backgrounds to central references on the disciplines he or she is not familiar with. The closing discussion delineates at what extent there are consensus, disputes and possibilities of policing among the varied approaches presented.
Keywords: R5; R1; Y80; A12; O2; 330